Cyanobacterial Peptides in Anticancer Therapy: A Comprehensive Review of Mechanisms, Clinical Advances, and Biotechnological Innovation - Heayyean Lee; Khuld Nihan; Yale Ryan Kwon (Marine Drugs, 2025)
Cyanobacteria-derived peptides represent a promising class of anticancer agents due to their structural diversity and potent bioactivity. They exert cytotoxic effects through mechanisms including microtubule disruption, histone deacetylase inhibition, and apoptosis induction. Several peptides—most notably the dolastatin-derived auristatins—have achieved clinical success as cytotoxic payloads in antibody–drug conjugates (ADCs). However, challenges such as limited tumor selectivity, systemic toxicity, and production scalability remain barriers to broader application. Recent advances in targeted delivery technologies, combination therapy strategies, synthetic biology, and genome mining offer promising solutions. Emerging data from preclinical and clinical studies highlight their therapeutic potential, particularly in treatment-resistant cancers. In this review, we (i) summarize key cyanobacterial peptides and their molecular mechanisms of action, (ii) examine progress toward clinical translation, and (iii) explore biotechnological approaches enabling sustainable production and structural diversification. We also discuss future directions for enhancing specificity and the therapeutic index to fully exploit the potential of these marine-derived peptides in oncology.